2021
DOI: 10.1017/s0022377821000222
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation study of impurity transport response to RMPs in RF-heated H-mode plasmas at EAST

Abstract: Spatial profiles of impurity emission measurements in the extreme ultraviolet (EUV) spectroscopic range in radiofrequency (RF)-heated discharges are combined with one-dimensional and three-dimensional transport simulations to study the effects of resonant magnetic perturbations (RMPs) on core impurity accumulation at EAST. The amount of impurity line emission mitigation by RMPs appears to be correlated with the ion Z for lithium, carbon, iron and tungsten monitored, i.e. stronger suppression of accumulation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Various studies have reported the transport change with edge magnetic island [13,14,19]. One idea is that the enhanced transport is due to the higher radial fraction of the parallel transport with the modified magnetic field topology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have reported the transport change with edge magnetic island [13,14,19]. One idea is that the enhanced transport is due to the higher radial fraction of the parallel transport with the modified magnetic field topology.…”
Section: Discussionmentioning
confidence: 99%
“…Under the same regime, impurity behavior has also been found to be effectively affected by RMP on various devices [13][14][15]. It is widely reported that the impurity concentration is reduced with the introduction of RMP in both L-and H-mode plasma.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, the measurement of the impurity radiation and profile near the X-point is also very important for stable radiative divertor operations. In addition, previous studies have shown that RMP is an effective way to suppress impurity accumulation in the plasma [4,5]. According to the simulation results with impurity transport code EMC3-EIRENE, the impurity profile from the divertor area clearly changes as RMP is applied [6].…”
Section: Introductionmentioning
confidence: 92%
“…The impurity transport code STRAHL calculates the radial density and radiation distributions of impurity in the core plasma, which has been applied to many fusion devices, including AUG [43], TCV [44], ADITYA [45], HL-2A [46], EAST [47,48], DIII-D [49]. The STRAHL code solves a coupled impurity particle conservation equation for each ionization stage [50,51],…”
Section: Strahl Modellingmentioning
confidence: 99%